Identification and characterization of the capsule depolymerase Dpo27 from phage IME-Ap7 specific to Acinetobacter pittii - Wang, Rentao; Liu, Yannan; Zhang, Yaqian; Yu, Shijun; Zhuo, Hailong; Huang, Yong; Lyu, Jinhui; Lin, Yu; Zhang, Xianglilan; Mi, Zhiqiang; Liu, Youning (Frontiers in Cellular and Infection Microbiology, 2024)
Among the Acinetobacter genus, Acinetobacter pittii stands out as an important opportunistic infection causative agent commonly found in hospital settings, which poses a serious threat to human health. Recently, the high prevalence of carbapenem-resistant A. pittii isolates has created significant therapeutic challenges for clinicians. Bacteriophages and their derived enzymes are promising therapeutic alternatives or adjuncts to antibiotics effective against multidrug-resistant bacterial infections. However, studies investigating the depolymerases specific to A. pittii strains are scarce. In this study, we identified and characterized a capsule depolymerase, Dpo27, encoded by the bacteriophage IME-Ap7, which targets A. pittii.A total of 23 clinical isolates of Acinetobacter spp. were identified as A. pittii (21.91%, 23/105), and seven A. pittii strains with various K locus (KL) types (KL14, KL32, KL38, KL111, KL163, KL207, and KL220) were used as host bacteria for phage screening. The lytic phage IME-Ap7 was isolated using A. pittii 7 (KL220) as an indicator bacterium and was observed for depolymerase activity. A putative tail fiber gene encoding a polysaccharide-degrading enzyme (Dpo27) was identified and expressed. The results of the modified single-spot assay showed that both A. pittii 7 and 1492 were sensitive to Dpo27, which was assigned the KL220 type. After incubation with Dpo27, A. pittii strain was susceptible to killing by human serum; moreover, the protein displayed no hemolytic activity against erythrocytes. Furthermore, the protein exhibited sustained activity across a wide pH range (5.0-10.0) and at temperatures between 20 and 50 °C. In summary, the identified capsule depolymerase Dpo27 holds promise as an alternative treatment for combating KL220-type A. pittii infections.